Genetic variability, adaptability and, stability of safflower genotypes developed for the Brazilian conditions by REML/BLUP - de Oliveira Neto, Sebastião Soares [UNESP]; Zeffa, Douglas Mariani; Ebertz, Odila Friss [UNESP]; Zoz, Tiago; Zanotto, Maurício Dutra [UNESP] (Wiley, 2021)
Safflower (Carthamus tinctorius L.) has stood out as an oilseed crop with potential for cultivation in Brazil and can be inserted in the already consolidated production systems. However, obtaining adapted genotypes is essential for crop development, and the study of genetic variability and agronomic performance in different regions contributes to the recommendation of new cultivars. However, the genotype × environment interaction can influence the selection and recommendation of a given genotype for a region of cultivation and hinder the breeder's work. The use of mixed models allows the evaluation of genotype performance without the influence of the genotype × environment interaction, which makes recommending a genotype for a region more accurate. Four experiments were carried out in different regions of Brazil (Bauru-SP, Botucatu-SP and, Campo Novo do Parecis-MT) to evaluate 10 safflower genotypes in the final stage of breeding. The genetic variability of genotypes was analyzed through similarity analysis, as well as the stability and adaptability of genotypes through mixed models. Wide variability was found between the evaluated genotypes. The use of mixed models allowed the identification of safflower genotypes with high stability and adaptability of the grain and oil yield for cultivation in Brazil.